Uses of sea buckthorn and its beneficial properties in medicine. - Narzullaeva Mehrangiz Azizkhonovna; Ibragimov Orif Madullaevich (Genius Journals, 2023)
The effectiveness of the sea buckthorn plant in medicine lies in the fact that this plant was used in ancient folk medicine for diseases of the lungs, liver, stomach and bones. In the conditions of Siberia, medicinal substances were prepared against dysentery, skin diseases, and rheumatism. In many ancient medical works, sea buckthorn was used against lung diseases. In addition, sea buckthorn preparations promote blood circulation in the body, and its fruits help in the treatment of throat diseases.
Keywords: Sea buckthorn fruits; medicine; vitamin